Systems as an Effort to Guarantee the Safety and Security of Guests Study of Hotel Building Fire Protection - Prastowo, Ichwan; Ari Indriastuti, Wahyu (ASTONJADRO, 2023)
Hotel fires can occur at any time without knowing the season for which the hotel building must have a fire extinguishing system that can guarantee the safety of guests, the purpose of this study is to find out the equipment used in the hotel building fire extinguishing system, to assess the completeness of facilities and infrastructure of the hotel building fire protection system, know the precautions against hotel fires in an effort to guarantee the safety and security of guests in hotel. The research methods used in this study are library study methods, interview methods, observation methods, documentation methods. Assessment of the completeness and reliability of building fire protection systems against fire hazards is used the parameters of tread completeness, means of rectification, active and passive protection systems. In data collection, it was carried out on the object of the study, namely at the Sahid Jaya Solo Hotel. The results of the discussion in this study, the equipment in the research object is complete and functions well and the results of the assessment of the reliability of the fire protection system obtained results of 90.63 which means that the reliability of the building is very good. From these results, it can be used as a consideration for the hotel in improving the right fire extinguishing system in an effort to guarantee the safety and security of guests.